National pathology day - Commemorating a legend Dr. VR Khanolkar - S Vijay Shankar; Saranya Singaravel; Aditya Agnihotri; Ranjan Agrawal (Wolters Kluwer Medknow Publications, 2022)
The large-scale celebration of National Pathology Day on the birth anniversary of Dr. VR Khanolkar would help pathologists to showcase their role in patient care, medical education, and research, change the image of pathology, and bring this specialty to the forefront.